Endometrial cancer prognosis correlates with the expression of L1CAM and miR34a biomarkers - Giacomo Corrado; Valentina Laquintana; Rossella Loria; Mariantonia Carosi; Laura de Salvo; Isabella Sperduti; Ashanti Zampa; Lucia Cicchillitti; Giulia Piaggio; Giuseppe Cutillo; Rita Falcioni; Enrico Vizza (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Background Patients with endometrial cancer (EC) and presumably with good prognosis may develop a recurrence indicating that the classification of this tumor is still not definitive and that new markers are needed to identify a subgroup at risk of relapse. The cell adhesion molecule L1CAM is highly expressed in several human carcinomas and has recently been described as a new marker for endometrial and ovarian carcinomas. The aim of this study was to determine the relevance of L1CAM in recurrent EC. Methods In this work we have analyzed, by immunohistochemical and RT-qPCR analysis, the expression of L1CAM in a cohort of 113 endometrial cancers at different stages, which 50% have relapsed. As a predictor of good outcome, the tumors were also analyzed for the expression of miR-34a, a post-transcriptional regulator of L1CAM. Results Among metastatic EC, the highest levels (60%) and the median level (24%) of L1CAM in tumors correlate with the progression, suggesting that the expression of this molecule is linked to the tumor component most involved in metastatic processes. We also found an inverse correlation between miR-34a and L1CAM protein expression, suggesting that miR-34a is a positive prognostic marker of EC. Conclusions Our results demonstrate the expression of L1CAM and miR-34a in EC as prognostic factors that identify subgroup of patients at high risk of recurrence suggesting for them more aggressive schedules of treatment.